APPLICATION OF BASALT FIBER IN AUTOMOTIVE PRIMERS: PROMISING RESEARCH AND FUTURE DIRECTIONS - Turayev , Azizbek (Techscience uz - Topical Issues of Technical Sciences, 2025)
Basalt fiber is recognized as a promising reinforcing material for automotive primers due to its high mechanical strength, thermal and chemical resistance, environmental friendliness, and economic efficiency. This combination of properties allows it to be considered not only for enhancing mechanical strength but also as an environmentally compliant and economically viable solution. This work examines the significant properties of basalt fiber for automotive primers, methods of its incorporation into primer matrices (including surface modification and dispersion technologies), and the operational properties of such composite coatings based on existing scientific sources.